Optimization of the Thickness, Water Vapour Transmission Rate and Morphology of Protein-Based Films Incorporating Glycerol and Polyethylene Glycol Plasticizers - Fahrullah, Fahrullah; Kisworo, Djoko; Bulkaini, Bulkaini; Yulianto, Wahid; Wulandani, Baiq Rani Dewi; Haryanto, Haryanto; Azhary Noersidiq; Maslami, Vebera; Ulkiyah, Kalisom; Kartika, Kartika; Rahmawati, Lilik (Faculty of Animal Science, Universitas Brawijaya, 2024)
Edible film is a thin layer that can coat food products and protect them from physical, chemical, and microbiological disturbances. This study aimed to determine the effect of the concentration ratio and different plasticizers on the thickness, water vapour transmission rate, and morphology of protein-based edible films. The study used a completely randomized design with a factorial pattern. The experiment involved two factors: Factor A, which was the whey-gelatine concentration ratio, at three levels (A1 = 1:0.5; A2 = 1:0.75; A3 = 1:1); and Factor B, which was the plasticizer, at two levels (B1 = glycerol; B2 = polyethylene glycol (PEG)). The study revealed that the water vapour transmission rate was significantly affected (P<0.01) by the interaction between whey-gelatin and different types of plasticizers. Additionally, the film thickness was significantly affected (P<0.01) by the whey-gelatine ratio, and the water vapour transmission rate was significantly affected (P<0.01) by the different types of plasticizers used. The film made from protein had a thickness of 0.282-0.357 mm, a water vapour transmission rate of 4.27-5.55 g/mm2.h, and a homogeneous surface structure resulting from the good mixing of whey and gelatin. The concentration of whey-gelatine and the use of different plasticizers can affect the thickness, WVTR, and morphology of the film. The use of glycerol as a plasticizer resulted in a greater thickness, water vapour transmission rate (WVTR), and morphology compared to those of the PEG plasticizer when the whey-gelatin concentration was 1:1.